Integrating Classical Jurisprudence and Modern Medicine: A Comprehensive Study of Menstruation, Postpartum Bleeding, and Chronic Vaginal Discharge in Islamic Law - Isrun Abdurahman; Harsing Harsing; Irfan Alkhotiri (STAI Minhajul Haq, 2026)
This article provides an in-depth analysis of the legal rulings (ahkam) surrounding women's natural blood—namely menstruation (haid), postpartum bleeding (nifas), and irregular bleeding (istihadhah)—by synthesizing classical Islamic jurisprudence (turath) with contemporary medical science. Within the Islamic tradition, the accurate identification of these blood types is not merely a biological concern but a fundamental requirement for the validity of ritual worship (ibadah), including prayer, fasting, and pilgrimage. Through a comparative study of the four major Sunni schools of thought (Hanafi, Maliki, Shafi'i, and Hanbali), this research highlights the diversity of ijtihad regarding the duration, characteristics, and legal implications of vaginal discharge. Furthermore, the study integrates modern physiological understandings of the uterine cycle and lochia to provide a more holistic framework for Muslim women in the contemporary era. Special attention is given to the use of menstrual delay medications for religious purposes and the psychological impact of ritual exclusion. The findings emphasize the necessity of a multidisciplinary approach that bridges the gap between religious literacy and reproductive health education to ensure spiritual well-being and legal certainty for Muslim women.